FINANCIAL PERFORMANCE OF BANK SYARIAH INDONESIA AFTER MERGER: A COMPARISON OF INCOME STATEMENT AND VALUE- ADDED APPROACHES FROM A SHARIA ENTERPRISE THEORY PERSPECTIVE - Yulianti, Lina; Mudzakir, Ahmad; Indrayani Rambe, Seprina; Sophan Himawan, Irfan (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2026)
This study examines the financial performance of Bank Syariah Indonesia (BSI) after the merger by comparing the Income Statement Approach and the Value-Added Approach from the perspective of Sharia Enterprise Theory. The merger of three state-owned Islamic banks represents a strategic transformation that requires a comprehensive performance evaluation beyond conventional profit-based measures.  Using secondary data from BSI’s annual financial statements for the period 2020-2024, this study analyses profitability and efficiency indicators, including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and the Operating Expenses to Operating Income Ratio (BOPO). A paired sample t-test is employed to examine differences between the two performance measurement approaches. The results indicate that BSI experienced short-term performance adjustments in the early post-merger period, followed by gradual improvements in profitability and operational efficiency. The Value-Added Approach consistently produces higher profitability ratios than the Income Statement Approach, reflecting its broader measurement scope that captures value creation and distribution to multiple stakeholders. Statistically significant differences are found for ROA, ROE, and NPM, while no significant difference is observed for BOPO. Practically, the findings provide insights for Islamic bank management in evaluating post-merger performance, support regulators in promoting performance assessment aligned with Sharia principles, and highlight the relevance of value-added-based measurement for enhancing stakeholder accountability in Islamic banking institutions.